Evaluating Alternative Approaches to Poverty Alleviation : Rice Tariffs Versus Targeted Transfers in Madagascar - Dorosh, Paul A.; Coady, David; Minten, Bart. (Washington, D.C. : International Monetary Fund, 2008)
This paper uses a partial equilibrium framework to evaluate the relative efficiency, distributional and revenue implications of rice tariffs and targeted transfers in Madagascar, especially in the context of identifying their respective roles for poverty alleviation. Although there are likely to be substantial efficiency gains from tariff reductions, these accrue mainly to higher income households. In addition, poor net rice sellers will lose from lower tariffs. Developing a system of well designed and implemented targeted direct transfers to poor households is thus likely to be a substantially more costeffective approach to poverty alleviation. Such an approach should be financed by switching revenue raising from rice tariffs to more efficient tax instruments. These policy conclusions are likely to be robust to the incorporation of general equilibrium considerations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet